IMPLEMENTATION OF DIGITAL TOURISM MARKETING PROGRAMS IN THE ERA OF INDUSTRIAL 4.0 BY DEPARTMENT OF TOURISM AND CREATIVE ECONOMY IN CIREBON CITY - Sukmadi, Sukmadi; Wisnu Bawa Tarunajaya; Ananta Budhi Danurdara; Hafizah Binti Hassan (International Journal of Social Science, 2024)
Tourism is a leading sector that has a positive impact on development on all fronts, both from a socio-cultural perspective, especially in terms of economic growth. At this time, the industrial revolution has reached industry 4.0. In this era, internet users in the world are increasing from year to year. As one of the sectors that plays a very important role in the economy of Cirebon City, namely the tourism sector, it is also necessary to use methods digital marketing in terms of marketing. With digital marketing, tourist attractions, culinary, cultural and everything related to tourism which has its own charm and appeal can be promoted quickly and widely with the help of the internet network. Tourism marketing carried out by the Cirebon City government has actually implemented digital marketing, but this application is only limited to social media and is still less active in marketing tourism in Cirebon City. In this research, the author used descriptive qualitative research methods. Data collection techniques were carried out by means of observation, interviews and documentation. Based on the tourism digital marketing program, it has been implemented by the Department of Tourism and Creative Economy, but because there are still several obstacles, this program cannot run optimally. This is in accordance with the results of the author's research using implementation theory from Van Meter and Van Horn, for the dimensions of policy size and objectives, characteristics of implementing agents, attitudes/dispositions of implementers, inter-organizational communication and implementing activities are considered to be good, whereas for the dimensions of resources and the economic, social and political environment are still not supportive